Divine powers and exchange with 'others' in Melanesia. (31st December 2021) - Hirsch, Eric
Abstract: Marshall Sahlins described divine king forms for a wide range of societies from Southeast Asia, Africa, and the Pacific, among others. In this article, I document a divine king form among the Fuyuge people of the Papuan highlands, revising my previous understanding of this powerful figure. At the same time, I argue there is an inextricable connection between Sahlins's theory of divine power and Marilyn Strathern's model of Melanesian gift exchange: both operate according to distinct ideas of otherness. The capacity to engage in transaction derives from cosmological sources while evidence of cosmological power is provided by the ability to engage in transactions with others in effective and powerful ways. More generally, I argue that conventional Melanesian figures of big‐men, great men, and chiefs are all versions of the alterity of power in related political forms; each instantiates the mutual relations between cosmological and transactional otherness. Abstrait: Pouvoirs divins et échanges avec « les autres » en Mélanésie Résumé Marshall Sahlins a décrit des formes de rois divins dans des sociétés très diverses d'Asie du Sud‐Est, d'Afrique et du Pacifique, entre autres. Dans le présent article, l'auteur m'intéresse à une forme de roi divin chez les Fuyuge des hautes‐terres de Papouasie et reviens sur ma perception antérieure de cette figure de pouvoir. Dans le même temps, il avance qu'il existe un lien inextricable entre la théorie du pouvoir divin de Sahlins et le modèle d'échange de dons mélanésien de Marilyn Strathern : tous deux fonctionnent selon des idées distinctes de l'altérité. La capacité d'entrer dans la transaction est conférée par des sources cosmologiques, tandis que la preuve du pouvoir cosmologique est fournie par la capacité d'entrer en transaction avec les autres de manières efficace et puissante. Plus généralement, il soutient que les figures mélanésiennes conventionnelles des big‐men, des grands hommes et des chefs sont toutes des versions de l'altérité du pouvoir sous des formes politiques apparentées : chacune est une instanciation des relations mutuelles entre altérité cosmologique et altérité transactionnelle.